2021
DOI: 10.1139/cjm-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine in methicillin-resistant Staphylococcus aureus and in silico interaction with sortase A

Abstract: Methicillin-resistant <i>Staphylococcus aureus</i> (MRSA) is one of the main human pathogens and is responsible for many diseases ranging from skin infections to more invasive infections. These infections are dangerous and expensive to treat because these strains are resistant to a large number of conventional antibiotics. Having said that, Antibacterial effect of ketamine against MRSA strains, its mechanism of action and in silico interaction with sortase A was evaluated. The antibacterial effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…ketamine has also been demonstrated to be involved in the growth-inhibiting activity of serious infections acquired in hospitals, such as methicillin-resistant Staphylococcus aureus (MRSA). ( Coutinho et al, 2021 ). Also, our cohort's reduced length of hospital stay might have contributed to the overall risk of acquiring hospital infection owing to less exposure.…”
Section: Discussionmentioning
confidence: 99%
“…ketamine has also been demonstrated to be involved in the growth-inhibiting activity of serious infections acquired in hospitals, such as methicillin-resistant Staphylococcus aureus (MRSA). ( Coutinho et al, 2021 ). Also, our cohort's reduced length of hospital stay might have contributed to the overall risk of acquiring hospital infection owing to less exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is responsible for the acquisition of iron from host cells, the adhesion of bacteria to the extracellular matrix of the host, and the evasion of its immune system. A similar mechanism of antibacterial activity occurs in the case of lidocaine and procaine, these damage the bacterial cell membrane, leading to changes in permeability and ion outflow within the bacterial cell (Coutinho et al, 2021). An ongoing clinical trial (NCT04843982, in the recruitment phase) aims to evaluate the anti-inflammatory effect of one of the ketamine stereoisomers in the acute phase of sepsis.…”
Section: Drugs Used In General and Local Anesthesiamentioning
confidence: 99%
“…Some anesthetic drugs also have antimicrobial activity. In vitro, studies have confirmed the effectiveness of ketamine against strains of P. aeruginosa, E. faecalis, S. pyogenes, S. epidermidis and S. aureus, including those resistant to methicillin (Begec et al, 2013;Coutinho et al, 2021;Sokolowska et al, 2023). The drug is believed to induce apoptosis by altering the integrity of the cell membrane and damaging bacterial DNA.…”
Section: Drugs Used In General and Local Anesthesiamentioning
confidence: 99%